Evaluation of public R&D policies: A cross-country comparison - Dirk Czarnitzki; Cindy Lopes Bento (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
This study focuses on the effect of public funding on internal R&D investment and on total innovation intensity on a cross-country comparative level. Using harmonised micro data from five different countries, this study analyzes the heterogeneity of the use of policy instruments. Applying a nonparametric matching method to identify the treatment effect, we find that on average firms would have invested significantly less if they would not have received subsidies. On similar grounds, our estimation also takes into account the 'treatment effects on the untreated'. This estimation enables us to assess whether or not governments could further foster R&D activities by extending innovation policies to currently not supported firms. With the exception of one country, all the governments of the sample would benefit from an extension of their subsidy policies. Finally, these two matching results can be combined in order to test for misallocation of public funds. Our analysis does not uncover any systematic misallocation of public funding for the countries under review.
Keywords: O38; 330; Innovation; Policy Evaluation; Treatment Effects; Cross-country comparison; Forschungssubvention; Wirkungsanalyse; Industrielle Forschung; Innovation; Investition; Schätzung; Belgien; Deutschland; Luxemburg; Südafrika; Spanien